The effect of the antidepressant venlafaxine on gene expression of biotransformation enzymes in zebrafish (Danio rerio) embryos - Hodkovicova, Nikola; Sehonova, Pavla; Blahova, Jana; Faldyna, Martin; Marsalek, Petr; Mikula, Premysl; Chloupek, Petr; Dobsikova, Radka; Vecerek, Vladimir; Vicenova, Monika; Vosmerova, Petra; Svobodova, Zdenka (Environmental science and pollution research international, 2020)
The effect of venlafaxine, a pharmaceutical commonly found in aquatic environment, was analyzed on non-target organism, Danio rerio (Hamilton, 1822). D. rerio embryos were treated by two different concentrations of venlafaxine: either concentration relevant in aquatic environment (0.3 μg/L) or concentration that was two orders of magnitude higher (30 μg/L) for the evaluation of dose-dependent effect. Time-dependent effect was rated at 24, 96, and 144 h post-fertilization (hpf). For gene expression, genes representing one of the phases of xenobiotic biotransformation (0 to III) were selected. The results of this study showed that the effect of venlafaxine on the zebrafish embryos is the most evident at hatching (96 hpf). At this time, the results showed a downregulation of gene expression in each phase of biotransformation and in both tested concentrations. In contrast, an upregulation of most of the genes was observed 144 hpf for both tested venlafaxine concentrations. The study shows that venlafaxine can affect the gene expression of biotransformation enzymes in D. rerio embryos even in the environmentally relevant concentration and thus disrupt the process of biotransformation. Moreover, the pxr regulation of genes seems to be disrupted after venlafaxine exposure in dose- and time-dependent manner.
Keywords: embryo nesavčí; Biotransformation; Embryo, Nonmammalian; regulace genové exprese enzymů; antidepresiva; Antidepressive Agents: ABC transporters; dánio pruhované; Xenobiotics; zvířata; Pharmaceutical; Regulation; Zebrafish; Metabolism; pxr; Water Pollutants, Chemical; biotransformace; Venlafaxine Hydrochloride; Gene Expression Regulation, Enzymologic; venlafaxin hydrochlorid; Animals; chemické látky znečišťující vodu